PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN KELOMPOKTANI DI DESA KEMUNING MUDA KECAMATAN BUNGARAYA KABUPATEN SIAK - Siti Nurjanah; Cepriadi Cepriadi; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Agricultural extension as part of the national life (especially farmers) and promote welfare in general is one key to success in order to strengthen farmer groups. Many farmers' groups have been developed, but there are many who questioned its existence. the purpose of this study was (1) Determine the role of agricultural extension in the village Kemuning muda. (2) Determine the development of farmers 'groups in the village Kemuning Muda, and (3) To identify any problems encountered by farmers in agricultural extension role in the development of farmers' groups in rural districts KemuningMuda Bungaraya Siak district. the method used in this research is survey method with a sampling technique that with Purposive Samplingmethod. the number of samples in this study were 6 farmer groups, respectively 5 samples taken farmer groups so that the total is 30 samples. data analysis using a Likert scale. the results showed that, the role of agricultural extension in the development of farmers' groups in rural districts KemuningMuda Bungaraya Siak district is quite good. handling problems faced by farmers in agricultural extension role in the development of farmer groups are less helpful extension of market access for agricultural products and the insufficient number of members who abide by the regulations. Keywords: Role Of Extension, Farmer Groups, Rice Farmers